Advances in quantitative analysis of finance and accounting. -- vol. 1 (1991- ). (Greenwich, Conn. JAI Press, 1991)
Annual
Annual.
Vols. for 1991- issued in 2 pts.
Keywords: Finance -- Mathematical models -- Periodicals; Accounting -- Mathematical models -- Periodicals